PERBANDINGAN KONTAMINASI PROTOZOA USUS SUMUR GALI DENGAN SUMUR POMPA TANGAN BERDASARKAN KONDISI FISIK DI KECAMATAN JELBUK KABUPATEN JEMBER - Syamsuddin, Alif Fazduani; Bagus Hermansyah; Jauhani, M. Afiful; Armiyanti, Yunita; Utami, Wiwien Sugih (Universitas Islam Negeri Alauddin Makassar, 2024)
Diarrhea is still a significant problem for people around the world. Diarrhea, a water-borne disease, can be caused by one type of parasite, namely intestinal protozoa. Intestinal protozoa can contaminate water sanitation if their hygiene is not maintained properly. This study’s purpose was to comparison of protozoal intestinal contamination of dug wells with hand pump wells based on physical conditions in Jelbuk District, Jember Regency. This study is an observational analytic study with a cross-sectional design. This study used primary data on the physical condition of dug wells and hand pump wells. The sedimentation method obtained primary data on intestinal protozoa contamination by microscopic detection. This study obtained 36 well water samples consisting of 30 dug wells and 6 hand pump wells. Entamoeba histolytica found in 4 dug wells (11.1%) is the type of intestinal protozoa that contaminates. This study concludes that there is a difference in contamination between dug wells and hand-pumped wells because the intestinal protozoan type Entamoeba histolytica is only found in dug well, but statistically, there is no difference in contamination between dug wells and hand-pumped wells.